Research on Magnetron Generator Energy Efficiency in Microwave Heating Devices - V. A. Ivanov; K. V. Rogozhin; D. S. Sidorenko (Известия высших учебных заведений России: Радиоэлектроника)
The crucial task when summarizing magnetron power in microwave technological installations is tracking of load optimality for individual generators. The article presents a method for estimating the efficiency of magnetron generator based on the current waveform in the anode supply circuit. It is found that the change in the third harmonic current phase in the Fourier expansion and the ratio of the two current extrema adequately reflect the magnetron load change by the high-frequency path. The statement verification is carried out on an experimental setup that allows to purposefully change the reflection of coefficient from the load and compare it with the current change in the high voltage circuit. Studies are carried out for the voltagedoubling scheme. To record changes in the current waveform due to the nonlinearity of the high-voltage transformer, computer simulations are performed with the use of LTSpice program. The LG Magnetron LG 2M214 with an output power of 1 kW is used as the object of research. The magnetron power supply and control board integrated in the general microprocessor control system, is developed and tested.